2016
DOI: 10.1002/chem.201504617
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of New Conjugated Fluorenyl‐Porphyrin Dendrimers for Optics

Abstract: A new family of conjugated meso-tetraphenylporphyrin-based dendrimers with four (TPP1, TPP2), eight (TPP3, TPP4, TPP5) and up to sixteen (TPP6) fluorenyl groups has been synthesized and fully characterized. These tetraphenylporphyrin-cored dendrimers present peripheral alkynyl π-conjugated dendrons with fluorenyl termini. The meso-aryl rings of these porphyrins are functionalized either in para- (TPP1, TPP2, and TPP3) or meta-positions (TPP4, TPP5, and TPP6). Their detailed luminescence properties are discusse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 54 publications
3
43
0
Order By: Relevance
“…Although the emission quantum yields are slightly diminished compared with that of the smaller TFP reference compound, we have shown that the brightness of TPP1 and TPP2 (expressed as ϵ × Φ F ) was much improved over that of TFP, a feature of interest for many applications. More interestingly, we have also provided evidenced that these dendrimers present remarkable two‐photon absorption (TPA) cross‐sections, which were significantly larger than those of TPP, especially in the case of compounds with fully conjugated arms, and that TPP1 and TPP2 sensitize oxygen quite efficiently . When taken together, these various observations strongly suggest that, once suitably functionalized, such molecular architectures (or closely related structures) might give rise to outstanding photosensitizers for various biomedical applications typical of porphyrin derivatives, such as one‐ or two‐photon photodynamic therapy (PDT).…”
Section: Introductionmentioning
confidence: 75%
See 4 more Smart Citations
“…Although the emission quantum yields are slightly diminished compared with that of the smaller TFP reference compound, we have shown that the brightness of TPP1 and TPP2 (expressed as ϵ × Φ F ) was much improved over that of TFP, a feature of interest for many applications. More interestingly, we have also provided evidenced that these dendrimers present remarkable two‐photon absorption (TPA) cross‐sections, which were significantly larger than those of TPP, especially in the case of compounds with fully conjugated arms, and that TPP1 and TPP2 sensitize oxygen quite efficiently . When taken together, these various observations strongly suggest that, once suitably functionalized, such molecular architectures (or closely related structures) might give rise to outstanding photosensitizers for various biomedical applications typical of porphyrin derivatives, such as one‐ or two‐photon photodynamic therapy (PDT).…”
Section: Introductionmentioning
confidence: 75%
“…To synthetically access these new dendrimers, a strategy analogous to that previously used for the synthesis of TPP‐cored porphyrin dendrimers was adopted, which basically involves two steps; 1) the synthesis of dendritic aldehyde precursor, and 2) the formation of the porphyrin core by reaction with pyrrole …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations